Trade, productivity, innovation, and employment: Lessons from the impact of Chinese competition on manufacturing in Brazil - Mauricio Mesquita Moreira; Marisol Rodríguez Chatruc; Filipe Lage de Sousa; Federico Merchán (Inter-American Development Bank (IDB), 2020)
This paper uses the sudden surge in Chinese competition faced by Brazil's manufacturers in the 2000s to revisit the findings from the literature on how productivity, innovation, and employment were impacted by the Great Liberalizationa period of massive trade opening in the early 1990s in Latin America. Using manufacturing firm-level data and sectoral variation of Chinese competition, we focus on the most intense period of the shock -2000 to 2013- and on its procompetitive and employment effects. The results reinforce some of the key findings of the earlier literature, notably the positive, procompetitive effect of trade on total factor productivity (TFP). However, as in the 1990s, these gains do not seem to have been robust enough to prevent the countrys TFP performance from being dismal. Likewise, they seem to be more consistent with level effects than growth effects. Inconclusive results on innovation also seem to point in this direction. The estimated effects on employment point to a relatively small negative shock, not unlike that of the early 1990s, that was centered on low-skilled labor and was consistent with the countrys relative abundance of natural resources. Overall, the results seem to underline the limits of trade policy in boosting employment and long-term productivity growth. Policymakers should manage their expectations accordingly.
Keywords: F14; F16; F61; O47; 330; import competition; productivity; innovation; employment